Intersecting social identity and drone use in humanitarian contexts: Psychological insights for legal decisions and responsible innovation - Anastasia Kordoni; Mark Levine; Amel Bennaceur; Carlos Gavidia-Calderon; Bashar Nuseibeh (Journal of Responsible Technology)
While the technical and ethical challenges of using drones in Search-and-Rescue operations for transnationally displaced individuals have been explored, how drone footage can shape psychological processes at play and impact post-rescue legal decision-making has been overlooked. This paper investigates how transnationally displaced individuals' social identities are portrayed in court and the role of drone footage in reinforcing these identities. We conducted a discourse analysis of 11 open-access asylum and deportation cases following drone-assisted Search-and-Rescue operations at sea (2015–2021). Our results suggest two primary identity constructions: as victims and as traffickers, each underpinned by conflicting psychological processes. The defence portrayed the defendants through the lens of vulnerability, while the prosecution through unlawfulness. Psychological attributions of drone footage contributed differently to identity portrayal, influencing legal decisions regarding the status and entitlements of transnationally displaced individuals. We discuss the socio-ethical implications of these findings and propose a psychosocial account for responsible innovation in technology mediated humanitarian contexts.